2008
DOI: 10.1681/asn.2007070745
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning with Endoplasmic Reticulum Stress Ameliorates Mesangioproliferative Glomerulonephritis

Abstract: Accumulating evidence suggests a pathophysiologic role of endoplasmic reticulum (ER) stress in kidney disease. This study investigated the potential of therapeutic approaches targeting ER stress in the anti-Thy1 model of mesangioproliferative glomerulonephritis in rats. Immunohistochemistry and Western blotting showed a time-dependent increase in the expression of the ER stress-inducible chaperones glucose-regulated protein 78 (GRP78) and oxygen-related protein 150 in isolated glomeruli, especially in the glom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 37 publications
5
88
0
1
Order By: Relevance
“…To evaluate the beneficial effect of ER stress preconditioning in kidney disease, we investigated whether a non-nephrotoxic dose of the ER stress inducers tunicamycin or thapsigargin for preconditioning ameliorate the development of anti-Thy1 nephritis, a mesangioproliferative glomerulonephritis model. As we expected, disease progression was dramatically improved by preconditioning, in association with a decrease in microaneurysm formation, adhesion of Bowman's capsule to the tuft, and proteinuria (Inagi et al, 2008). Importantly, the protective effect of preconditioning against glomerular damage was associated with modulation of the adaptive UPR.…”
Section: Er Stress Preconditioningsupporting
confidence: 63%
See 1 more Smart Citation
“…To evaluate the beneficial effect of ER stress preconditioning in kidney disease, we investigated whether a non-nephrotoxic dose of the ER stress inducers tunicamycin or thapsigargin for preconditioning ameliorate the development of anti-Thy1 nephritis, a mesangioproliferative glomerulonephritis model. As we expected, disease progression was dramatically improved by preconditioning, in association with a decrease in microaneurysm formation, adhesion of Bowman's capsule to the tuft, and proteinuria (Inagi et al, 2008). Importantly, the protective effect of preconditioning against glomerular damage was associated with modulation of the adaptive UPR.…”
Section: Er Stress Preconditioningsupporting
confidence: 63%
“…We previously demonstrated that ER chaperone expression was significantly increased in the damaged mesangial area in anti-Thy1 nephritis rats, a representative mesangioproliferative glomerulonephritis model (Inagi et al, 2008). For example, immunohistochemistry for the detection of GRP78 and ORP150 followed by quantitative morphometry confirmed that the UPR for the induction of ER chaperone expression was markedly enhanced as the disease progressed.…”
Section: Mesangial Cells and Er Stressmentioning
confidence: 89%
“…3 Previous studies suggested that ER stress has the potential to activate NF-B and thereby contributes to the development of inflammation, as reviewed by Zhang and Kaufman 4 ; however, in the kidney, previous reports showed that UPR was induced in glomeruli of rats with passive Heymann nephritis and that ER stress preconditioning attenuated proteinuria in this experimental model. 5,6 Inagi et al 7 also reported that, in the anti-Thy1 model of mesangioproliferative glomerulonephritis in rats, UPR was induced in nephritic glomeruli, especially in podocytes and mesangial cells. They also showed that preconditioning with subnephritogenic doses of ER stress inducers ameliorated the pathologic manifestations of the disease; however, mechanisms underlying the anti-inflammatory potential of ER stress and UPR have not been elucidated.…”
mentioning
confidence: 98%
“…Beneficial effect of preconditioning with ER stress was demonstrated in an animal model of mesangioproliferative glomerulonephritis. 52 ER stress resulting from the application of a subnephritogenic dose of an ER stress inducer (TM or TG) induced the adaptive UPR. 26,52 Cytoprotection by ER stress preconditioning was also confirmed in cultured renal tubular cells exposed to nephrotoxic drugs via the induction of GRP78 and an enhancement of ER folding capacity.…”
Section: Discussionmentioning
confidence: 99%
“…52 ER stress resulting from the application of a subnephritogenic dose of an ER stress inducer (TM or TG) induced the adaptive UPR. 26,52 Cytoprotection by ER stress preconditioning was also confirmed in cultured renal tubular cells exposed to nephrotoxic drugs via the induction of GRP78 and an enhancement of ER folding capacity. [53][54][55] In this study, preconditioning targeting ER stress ameliorated TGF-β1-induced EMT and apoptosis in HPMCs, suggesting the role of ER as a potential target for protecting the peritoneal membrane.…”
Section: Discussionmentioning
confidence: 99%